Web-based learning courseware for autistic child: using video modelling and active learning techniques / Siti Fairuz Mohd Radzi - Mohd Radzi, Siti Fairuz (2014)
Most of learning coursewares that are available in store are developed for normal children and not for children with disabilities such as Autistic children who are known to have problem in learning especially when it comes to learning something that the child are not familiar with as well as the child tends to feel bored and frustrated easily. The child will simply throw away everything that is given to the child most of the time. The peculiar behaviours of the Autistic child become a hardship and problem to most parents and guardian associated with Autistic child. Thus, Autisware courseware is developed and implemented specially for children with Autistic disorder; one of the types of Autism Spectrum Disorder (ASD), as a solution to enhance the learning skills of the child and allow the child to be at par with other normal children. The implementation of Autisware courseware will help Autistic child to learn on how to use five common equipment; cup, spoon, shoes, toothbrush and pencil, as well as learn alphabets and numbers. The learning activities are made in an interactive way in order to avoid the Autistic child from boredom and frustration throughout the learning activity. In this project, video modelling and active learning techniques were utilized as both techniques are proven to be effective to improve Autistic child's learning skills. The analysis of the result concluded that the combination of video modelling and active learning techniques are able to engage the Autistic child throughout the learning activity and generate the child's brain to work actively as the child will be allowed to watch and imitate the activity in the videos as well as playing games provided in the courseware.